PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS VB DI SEKOLAH DASAR NEGERI 15 BUTON (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of the school environment on the character formation of Grade VB students at SD Negeri 15 Buton. The school environment in this study encompasses physical, social, and academic aspects. The research method used is quantitative with a survey approach. Data collection techniques are conducted through questionnaires distributed to all Grade VB students and direct observation within the school premises. Furthermore, the data are analyzed using simple linear regression tests. The results indicate that the school environment has a significant influence on student character formation, especially in the aspects of discipline, responsibility, and cooperation. There is a significant influence of the school environment on student character formation by 89%. This proves that a more conducive school environment leads to better character development in students, particularly regarding the values of discipline and responsibility. The conclusion of this study is that the school environment plays a crucial role in the moral formation of students at SD Negeri 15 Buton.